TARSIL as an educational value in Indonesian sports system - Zainudin Amali; Sumaryanto Sumaryanto; Mohammad Arif Ali; Gustiana Mega Anggita; Billy Castyana; Tandiyo Rahayu; Yusuf Suparman; Heny Setyawati; Said Junaidi; Donny Wira Yudha Kusuma (LPMPP Universitas Negeri Yogyakarta, 2021)
The implementation of national sports development must be in line with the national sports policies. TARSIL which is an abbreviation for trust, authority, responsibility, supervision, integration and local wisdom is considered as an ideal formula for policy making-regional autonomy related. The purpose of this study was to analyze the Indonesian Sports System (policy product) based on TARSIL values. This is a qualitative study whereby data were collected through observation, documentation, and interview. The Indonesian Sports System was used as the object of sports policy. Seven people actively participated in this study. Data analysis consisted of reduction, presentation, and conclusion drawing. The results showed that the Indonesian Sports System has been implementing TARSIL values. All components of TARSIL are stated in the Indonesian Sports System. However, not all indicators of those components were stated. We suggested that TARSIL values may be used as the consideration for the upcoming sports policies at either national or regional levels.